Analisis Implementasi Customer Relationship Management dan Marketing Public Relations terhadap Nilai Pelanggan dan Dampaknya terhadap Loyalitas Pelanggan: Studi Kasus Grand Tropic Suites’ Hotel - Natalia Natalia; Cooky Tri Adhikara; Shirley Agusthina (Bina Nusantara University, 2012)
The impact of the globalization resulted in the business world being colored by the increase of high competition. Because of that the perpetrators of the business must continue to maintain the continuity of his business and to try to look for the opportunity by making use of the superiority that was owned. One of the methods that could be followed was constructive the customer's loyalty by maintaining the available customer so as they were loyal and did not move to the other competitor. Therefore, it is important for the company to create the value of the superior for the customers. The case study was about Customer Relationship Management program (CRM) and Marketing Public Relations (MPR) that was carried out by Grand Tropic Suites’ Hotel to create the value of the superior of the customers where being expected with this superior value to be able to affect the customer to loyal to the Hotel. The aim of this research was to analyze the implementation of Customer Relationship Management programs (CRM) and Marketing Public Relations (MPR) towards the Perceived Value and it impact towards Customer Loyalty.